A Method for Detecting Fungal Contamination in Paperboard Cartons - J. A. Narciso; M. E. Parish (EDIS)
Contamination of refrigerated juice products in gable-top cartons may occur by filamentous fungi that are present in the paperboard. The method presently used by the food industry to assess the amount of fungal contamination in the paperboard carton material is cumbersome and inefficient (1). To ascertain what types of fungal organisms are present in paperboard containers used to hold foods and beverages with an extended shelf-life, a direct-plating method was developed which is efficient, accurate and utilizes little in the way of time and resources (2). This method incorporates routinely used mycological techniques, including medium and incubation procedures which insure that conditions for fungal growth are optimal and results will be reliable.  This document is FSHN04-07, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2004.